Double superstructures in InGaN/GaN nano-pyramid arrays. (October 2015) - Chang, Chiao-Yun; Li, Heng; Hong, Kuo-Bin; Yang, Ya-Yu; Lai, Wei-Chih; Lu, Tien-Chang
Highlights: InGaN/GaN superstructures were formed in one GaN pyramid by SAG. Double wavelength emissions from MQWs and NHD in GaN nano-pyramid. Superstructures showed extremely low QCSE, yielding great light emission efficiency. Abstract: We have fabricated and investigated InGaN/GaN nanopyramid arrays grown on c -plane sapphire by selective area growth technique. The double InGaN/GaN superstructures were formed in one GaN pyramid observed in transmittance emission microscopy. The two growth faces on GaN nanopyramind showed different growth rates, resulted in double superheterostructures of semi-polar facets for InGaN/GaN multiple quantum wells (MQWs) and c -plane InGaN/GaN nano-hetero-disk (NHD) under the nanoscale growth condition. The c -plane InGaN/GaN NHD had high Indium composition due to the pulling effect, exhibiting double wavelength emissions from GaN nanopyramid. And InGaN/GaN MQWs and c -plane InGaN/GaN NHD showed extremely low quantum confinement Stark effect, yielding great light emission efficiency. This result is beneficial for the development of blue, green and white light-emitting diodes.